Probing Concept of Critical Thinking in Nursing Education in Iran: A Concept Analysis - Mansooreh Tajvidi, PhD; Shahrzad Ghiyasvandian, PhD; Mahvash Salsali, PhD (Elsevier, 2014)
Purpose: Given the wide disagreement over the definition of critical thinking in different disciplines, defining and standardizing the concept according to the discipline of nursing is essential. Moreover, there is limited scientific evidence regarding critical thinking in the context of nursing in Iran. The aim of this study was to analyze and clarify the concept of critical thinking in nursing education in Iran. Methods: We employed the hybrid model to define the concept of critical thinking. The hybrid model has three interconnected phases-the theoretical phase, the fieldwork phase, and the final analytic phase. In the theoretical phase, we searched the online scientific databases (such as Elsevier, Wiley, CINAHL, Proquest, Ovid, and Springer as well as Iranian databases such as SID, Magiran, and Iranmedex). In the fieldwork phase, a purposive sample of 17 nursing faculties, PhD students, clinical instructors, and clinical nurses was recruited. Participants were interviewed by using an interview guide. In the analytical phase we compared the data from the theoretical and the fieldwork phases. Results: The concept of critical thinking had many different antecedents, attributes, and consequences. Antecedents, attributes, and consequences of critical thinking concept identified in the theoretical phase were in some ways different and in some way similar to antecedents, attributes, and consequences identified in the fieldwork phase. Finally critical thinking in nursing education in Iran was clarified. Conclusion: Critical thinking is a logical, situational, purposive, and outcome-oriented thinking process. It is an acquired and evolving ability which develops individually. Such thinking process could lead to the professional accountability, personal development, God's consent, conscience appeasement, and personality development.